Plasma enhanced growth of GaN single crystalline layers from Ga vapour1. Issue 4 (8th April 2013) - Zwierz, R.; Golka, S.; Kachel, K.; Siche, D.; Fornari, R.; Sennikov, P.; Vodopyanov, A.; Pipa, A. V.
Abstract We present an alternative approach to grow thick GaN single crystalline layers from Ga vapour, transported by an N2 carrier gas flow, and from nitrogen, excited very near the substrate by 2.45 GHz microwaves at pressure in the 200–800 mbar range. Crystal growth requires high stability of process parameters, especially of plasma operation. A major challenge arose from temperature dependent changes in cavity resonance. Optical emission spectroscopy (OES) was used for plasma characterization while the grown layers were characterized by scanning electron microscopy (SEM) and X‐ray diffraction (XRD).